Shallow water effect of pusher barge system - Aizat Fitri Rozaki, 1987-; Koh, Kho King, supervisor; Fakulti Kejuruteraan Mekanikal (2010)
Project Paper (Sarjana Muda (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2010